2015
DOI: 10.2466/30.24.pms.120v13x7
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Kayaking and Rowing Sports Experience on Postural Response to Optic Flow

Abstract: This study investigated the postural response of kayakers and rowers to imposed optic flow. The athletes, with experience in unstable water environments, should have a specific postural response to optic flow. 12 male participants with kayaking and rowing experience and 12 with no specific sports experience were asked to stand still with and without room motion. This study varied the amplitude and frequency of room motion and evaluated the trajectory of the center of pressure. The kayaking and rowing group wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Differences in handwriting between male and female children have been shown in some more recent studies ( Hystegge et al, 2012 ; Lange-Küttner and Ebersbach, 2012 ; Tabatabaey-Mashadi et al, 2015 ). Tabatabaey-Mashadi et al (2015 , p. 25) analyzed strategies of digitizing tablet drawing by 6–7-year-old children, and they reported that when these children draw a rhomboid, compared to boys, “girls pay more attention to details, and they tend to perform the polygon segment by segment rather than drawing it with fewer strokes.” Lange-Küttner and Ebersbach (2012) used a drawing cube task, and they reported that female children focus more on detail while male children focus more on shape. In a study on reading skills of 10-year-old children, Hystegge et al (2012 , p. 123) reported that “boys and girls differ with respect to the correlation between visual processing skills and reading performance” which confirmed the hypothesis based on the male advantage for visual memory skills.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Differences in handwriting between male and female children have been shown in some more recent studies ( Hystegge et al, 2012 ; Lange-Küttner and Ebersbach, 2012 ; Tabatabaey-Mashadi et al, 2015 ). Tabatabaey-Mashadi et al (2015 , p. 25) analyzed strategies of digitizing tablet drawing by 6–7-year-old children, and they reported that when these children draw a rhomboid, compared to boys, “girls pay more attention to details, and they tend to perform the polygon segment by segment rather than drawing it with fewer strokes.” Lange-Küttner and Ebersbach (2012) used a drawing cube task, and they reported that female children focus more on detail while male children focus more on shape. In a study on reading skills of 10-year-old children, Hystegge et al (2012 , p. 123) reported that “boys and girls differ with respect to the correlation between visual processing skills and reading performance” which confirmed the hypothesis based on the male advantage for visual memory skills.…”
Section: Introductionmentioning
confidence: 70%
“…Studies have also shown differences between male and female children in the development of visual cognition and in the relationships between visual cognition and other processes. Visual processes are associated with reading in male children, but not in female children ( Hystegge et al, 2012 ), and gender differences have also been observed for drawing ( Lange-Küttner and Ebersbach, 2012 ) and handwriting ( Tabatabaey-Mashadi et al, 2015 ). Therefore, we analyzed the data in the present study by considering the age and the gender as relevant factors in the development of handwriting skills.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that an important feature of hypervigilance is increased attending to somatosensory input at pain-relevant body locations ( Van Damme et al, 2016 ). This idea has been extensively investigated in a series of studies in healthy volunteers indicating that experimentally induced threat of pain on one specific location of the body resulted in increased attending to somatosensory stimuli at that body location relative to other areas ( Crombez et al, 1998 ; Durnez & Damme, 2015 ; Vanden Bulcke et al, 2013 ; Vanden Bulcke et al, 2014 ; Vanden Bulcke et al, 2015 ; Van Hulle et al, 2015 ; but see Durnez & Van Damme, 2016 , for a failed replication). Applied to unilateral TMD pain, one would expect enhanced attending to somatosensory information specifically at the painful side of the jaw.…”
Section: Introductionmentioning
confidence: 99%
“…42 A binary variable was created and coded as follows: 0=low PA (≤23 units; n=233), and 1=high PA (≥24 units; n=190). 43…”
Section: Methodsmentioning
confidence: 99%